Social work in the web of social protection: contexts and alternatives - Santos, C. P. C. D.; Valduga, T.; Ferreira, J. (International Social Work, 2020)
In the context of research in the field of social work, we have carried out an analysis on the relationship between two social policy measures intended to promote the social well-being of its beneficiaries in Portugal. Through a deductive methodology, the results show the impact of the adopted measures aimed at reducing spending on social policies. Conclusions highlight that social workers can collaborate with alternative social responses in an evidence-based manner, enhancing practice, namely, regarding competencies for the realisation of social diagnosis within the context of peoples’ living conditions in order to promote access of citizens to social support.